2017
DOI: 10.1007/s00268-017-4308-9
|View full text |Cite
|
Sign up to set email alerts
|

Less is More: The Impact of Multidisciplinary Thyroid Conference on the Treatment of Well‐Differentiated Thyroid Carcinoma

Abstract: In conjunction with implementation of a thyroid malignancy multidisciplinary conference, we observed significantly decreased postoperative dosing of RAI without increased tumor recurrence. The 2009 ATA guidelines were associated with a further decrease in RAI administration. Treatment for patients with thyroid carcinoma is optimized by a multidisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…This approach has also led to our adherence to guidelines, as has been reported by Moore et al in New York, where a similar change in RAI usage was reported following publication of the 2009 guidelines, with management decisions made within a multi-disciplinary environment. 20 The reduction in the use of RAI was accompanied by more aggressive surgery in our study, in particular, CLND. The indications for and the extent of lymph node dissection in DTC patients have always been controversial.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…This approach has also led to our adherence to guidelines, as has been reported by Moore et al in New York, where a similar change in RAI usage was reported following publication of the 2009 guidelines, with management decisions made within a multi-disciplinary environment. 20 The reduction in the use of RAI was accompanied by more aggressive surgery in our study, in particular, CLND. The indications for and the extent of lymph node dissection in DTC patients have always been controversial.…”
Section: Discussionsupporting
confidence: 46%
“…This approach has also led to our adherence to guidelines, as has been reported by Moore et al . in New York, where a similar change in RAI usage was reported following publication of the 2009 guidelines, with management decisions made within a multi‐disciplinary environment …”
Section: Discussionmentioning
confidence: 99%
“…In a study from the University of California, San Francisco, only 101 of 394 patients (25.6%) who underwent thyroid lobectomy between 2000 and 2010 should have had adjuvant radioactive iodine treatment according to the new ATA guidelines, whereas 59.6% had radioactive iodine treatment corresponding to the revised 2009 ATA guidelines . A recent study by Moore et al identified that multidisciplinary conferences with ATA guidelines implementation resulted in a decrease in radioactive iodine treatment rates without an increase in recurrence rates. Similarly, we found a large and clinically meaningful decrease in the use of radioactive iodine treatment in the 2016 cohort compared with the 2013 to 2014 cohort, and the data are compatible with a decrease as large as 38%.…”
Section: Discussionmentioning
confidence: 99%
“…An enlarged thyroid or nodules are common symptoms, and manifest as hard nodules of the thyroid, which can move up and down when swallowing. Radiation exposure, viral infection, or family inheritance can all be the triggers for DTC, especially for people with a history of radioactive exposure, and the risk of disease is significantly increased (11). DTC accounts for more than 90% of thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%